L'enseignement de la conjugaison en français langue étrangère : représentations et pratiques déclarées d'enseignants novices - Guerif, Noémie (My University, 2017)
Like Ulma and Lepoire-Duc who state that "the field of the verb is (...) for students and teachers alike, the place of all issues" (2010: 11), we think it is the same for novice teachers of French as a foreign language (FFL). Thus, the purpose of our research is to identify the difficulties that these teachers face in class when they are led to talk about verbal morphology, i.e. conjugation. To do so, we interviewed five recently graduated teachers of French as a foreign language through semi-guided interviews. The collected speeches, in that they allow the emergence of representations and proclaimed teaching practises, reveal obstacles regarding the material taught as well as teaching practices, the latter being partly influenced by the different students' profiles in front of them. Besides, we notice that the personal background of each of our teachers as learners is entirely part of their teaching repertoire.
Keywords: teaching French as a foreign language; French verb morphology; representations; proclaimed practices; teaching repertoire